Предмет: Алгебра,
автор: vicky2000
(3-x)(x+3)=x(4-x)
Решите,СРОЧНО НАДО!!
Ответы
Автор ответа:
0
(3-х)*(х+3)=х*(4-х)
3х-х2+9-3х=4х-х2
-х2+9-4х+х2=0
-4х=-9
4х=9
х=94
х=2,25
Проверка
(3-2,25)*(2,25+3)=2,25*(4-2,25)
0,75*5,25=2,25*1,75
3,9375=3,9375
3х-х2+9-3х=4х-х2
-х2+9-4х+х2=0
-4х=-9
4х=9
х=94
х=2,25
Проверка
(3-2,25)*(2,25+3)=2,25*(4-2,25)
0,75*5,25=2,25*1,75
3,9375=3,9375
Похожие вопросы
Предмет: Химия,
автор: Kisl1k
Предмет: Русский язык,
автор: nisathamidov
Предмет: Английский язык,
автор: kkoroleva567
Предмет: Химия,
автор: Воронесса